SOSIALISASI DAN PELATIHAN 5S (SEIRI, SEITON, SEISO, SEIKETSU, DAN SHITSUKE) UNTUK PENINGKATAN EFISIENSI USAHA GAS LPG - Christine Natalia; Trifenaus Prabu Hidayat; Andre Sugioko (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2018)
Pangkalan Puskop Bintara LPG located in East Jakarta is one of the official bases of Pertamina which provides LPG sizes of 3 kg and 12 kg. The rotation of the availability and distribution of gases at the Puskop Bintara LPG Base is very fast. However, this is not supported by conditions in the workplace area that have not been well organized. Based on observations in the field, the problems related to the work area, namely the condition of the base is not clean, gas laying that is not in accordance with the layout of gas storage, and the discipline of employees related to cleanliness is still lacking. To overcome these problems, the best solution is to apply 5S, which is sorting (Seiri), arrangement (Seiton), cleaning (Seiso), maintaining good conditions (Seiketsu), and self-awareness of the habits needed to do the job properly (Shitsuke ) The community service method is carried out through the dissemination of the 5S concept and its application such as: sorting goods and disposing of seals (Seiri), placing LPG gas cylinders neatly and regularly both still filled with gas and empty with instructions on the location and name of gas cylinders LPG (Seiton), cleaning LPG seal waste scattered on the floor and cleaning LPG bases on a regular basis (Seiso), making 5S socialization posters for workers as a reminder in maintaining the work area and arranging LPG gas cylinders neatly (Shitsuke). The result of 5S implementation is an increase in understanding the importance of 5S in improving work efficiency and productivity as well as increasing comfort and neatness in the work area.